Strike-slip related folding within the Malvinas/Falkland Trough (south-western Atlantic ocean) - Esteban, Federico Damián (2020)
The Malvinas/Falkland Trough (M/FT) is an E-W trending bathymetric depression along which runs the present-day South American-Scotia plate boundary. To the north of the M/FT lies the southern sector of the South Malvinas/Falkland Basin, and to the south lies the Burdwood Bank, an elongated morphological high constituting part of the South Scotia Ridge. Analysis of bathymetric and slope maps, integrated with seismic reflection profiles, have allowed describing in detail the M/FT in the sector comprised between 60° and 57° W. Data show the presence of an array of folds forming a thin-skinned fold-and-thrust Belt (FTB), previously interpreted as an active compressional field. The thin-skinned FTB is developed in a triangular-shaped area, which extends ca. 100 km in the E-W direction and 16 km in the N-S direction. Four parallel, asymmetric folds that develop to progressively greater water depths (between 1600 and 2600 m depth) towards the north, with orientations ESE-WNW and lengths that vary between 22 and 98 km, have been recognized. These folds are constituted by Late Cenozoic sediments that are undeformed in the Malvinas/Falkland Trough. The development of folds, which began in the late Miocene (ca. 7 Ma), was associated with the left-lateral strike-slip tectonic regime of the Magallanes-Fagnano-Malvinas lineament, the western segment of the South American-Scotia plate boundary.